Reaction Shallot Growth and Production to Water Hyacinth LOF Provisioning - Rosdiana, Rosdiana; Ismunandar, Ismunandar; Wulandar, Yukarie i Ayu; Putri, Dirgahani (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Water hyacinth (Eichornia crassipes) is the potential material for an organic fertilizer either liquid or solid form. A plant with significant commercial importance is the red onion (Allium ascalonicum L.). The study's objective was to ascertain how shallot growth and production affected the provision of water hyacinth LOF. The research was carried out at the Lebak Bulus Nursery, Center for Seed Development and Plant Protection, Department of Maritime Affairs, Agriculture and Security of Food, DKI Jakarta in February 2022 to May 2022. The research design used was RCBD utilizing five replications and five treatments. The treatmens were water hyacinth LOF at a dose of 0, 60 , 90, 120, and 150 ml/plant. The variables observed were plant height, leaf count, tuber count, diameter of tubers, gross weight, and consumption weight. The results of this research indicated that the dosage of water hyacinth liquid organic fertilizer of 60 up to 120 ml/plant had not be able to provide different results compared to controls for vegetative variables and shallot production.